PELATIHAN PROMOSI BERBASIS MEDIA SOSIAL PADA UMKM BAWANG GORENG RIA JUNA - Raja Sharah Fatricia; Dessy Elliyana (Jurnal Publika Pengabdian Masyarakat, 2019)
One of the UMKM in Jambi Province is Fried Onions UMKM. The number of UMKM producers on fried onions but among them does not have a broad means of promotion, namely through social media. Due to the fast growing business of fried onions, fried onions are also selling to sell their products from one place to another, even within a considerable distance. This Juna fried onion UMKM has considerable potential for them to still carry out conventional promotions by word of mouth, even though promotion is an important aspect of marketing to inform products to consumers.Keywords: Training, Promotion, UMKM